Biodegradation of polycyclic aromatic hydrocarbons by a bacterial consortium enriched from mangrove sediments - Shahriari Moghadam, Mohsen (J Environ Health Sci Eng, 2014)
Polycyclic aromatic hydrocarbons (PAHs) biodegradation in contaminated sediment is an attractive remediation technique and its success depends on the optimal condition for the PAH-degrading isolates. The aims of the current study was to isolate and identify PAHs-degrading bacteria from surface sediments of Nayband Bay and to evaluate the efficiency of statistically based experimental design for the optimization of phenanthrene (Phe) and Fluorene (Flu) biodegradation performed by enriched consortium. PAHs degrading bacteria were isolated from surface sediments. Purified strains were then identified by 16S rDNA gene sequence analysis. Taguchi L(16) (4(5)) was employed to evaluate the optimum biodegradation of Phe and Flu by the enriched consortium. Total of six gram-negative bacterial strains including Marinobacter hydrocarbonoclasticus, Roseovarius pacificus, Pseudidiomarina sediminum and 3 unidentified strains were isolated from enrichment consortium, using Fluorene (Flu) and phenanthrene (Phe) as the sole carbon and energy source. The enriched consortium showed highest degradation abilities (64.0% Flu and 58.4% Phe degraded in 7 days) in comparison to a single strain cultures or mixtures. Maximum biodegradation efficiency was occur at temperature = 35°C; pH = 8; inoculum size = 0. 4 OD(600nm); salinity = 40 ppt; C/N ratio = 100:10. In conclusion our results showed that, indigenous bacteria from mangrove surface sediments of Nayband Bay have high potential to degrade Flu and Phe with the best results achieved when enriched consortium was used.